An Updated Overview of the Magnetic Resonance Imaging of Brain Iron in Movement Disorders. (24th February 2022) - Tambasco, Nicola; Nigro, Pasquale; Chiappiniello, Andrea; Paolini Paoletti, Federico; Scialpi, Sara; Simoni, Simone; Chiarini, Pietro; Parnetti, Lucilla
Abstract : Brain iron load is one of the most important neuropathological hallmarks in movement disorders. Specifically, the iron provides most of the paramagnetic metal signals in the brain and its accumulation seems to play a key role, although not completely explained, in the degeneration of the basal ganglia, as well as other brain structures. Moreover, iron distribution patterns have been implicated in depicting different movement disorders. This work reviewed current literature on Magnetic Resonance Imaging for Brain Iron Detection and Quantification (MRI-BIDQ) in neurodegenerative processes underlying movement disorders.